AUTOMATED CATARACT DETECTION SYSTEM: A MACHINE LEARNING APPROACH FOR EARLY DIAGNOS AND INTERVENTION - Rawat, Vishal; Mishra, Harshita; Rajak, Rajbeer; Thakur, Rashmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Cataracts, a leading cause of vision impairment, present a significant global health concern affecting millions of individuals. In response to this issue, this paper introduces a groundbreaking approach to cataract detection, harnessing the power of machine learning and artificial intelligence (AI) to enable early diagnosis and personalized treatment. The proposed methodology encompasses a meticulously designed process, commencing with the systematic collection and preprocessing of pertinent data. Subsequently, Convolutional Neural Networks (CNNs) are employed for intricate image analysis, providing a robust foundation for the detection of cataracts. Beyond conventional methods, the approach incorporates innovative clustering techniques to delve deeper into the intricacies of cataract subtypes and stages. This nuanced understanding enhances the system’s capability to discern subtle variations, thus contributing to more accurate and tailored identification of cataracts. Notably, this system is strategically designed to be applicable in regions with limited medical resources, aiming to provide a cost-effective and accessible means of cataract identification. The integration of AI and clustering methodologies within this system presents a holistic solution to alleviate the global burden of cataracts. By facilitating timely medical intervention, the proposed system endeavors to mitigate the long-term impact on affected individuals. Through this innovative amalgamation of advanced technologies, the automated cataract detection system strives to redefine the landscape of ophthalmic diagnostics, marking a significant stride towards enhanced healthcare accessibility and efficiency on a global scale.